Comparison of the analytical performance between the Oncomine Dx Target Test and a conventional single gene test for epidermal growth factor receptor mutation in non‐small cell lung cancer. Issue 4 (12th December 2020) - Sakaguchi, Tadashi; Iketani, Akemi; Furuhashi, Kazuki; Nakamura, Yuki; Suzuki, Yuta; Ito, Kentaro; Fujiwara, Kentaro; Nishii, Yoichi; Katsuta, Koji; Taguchi, Osamu; Hataji, Osamu
Abstract: Background: Next‐generation sequencing (NGS) has been implemented in clinical oncology to analyze multiple genes and to guide targeted therapy; however, little is known about the performance of the Oncomine Dx Target Test compared with conventional single gene tests for detecting EGFR mutations. The objective of this study was to evaluate the performance of the Oncomine Dx Target Test compared with a PNA‐LNA PCR clamp test to detect EGFR mutations. Methods: We retrospectively reviewed consecutive patients with non‐small cell lung cancer (NSCLC) from whom FFPE samples were simultaneously submitted for the Oncomine Dx Target Test, and a PNA‐LNA PCR clamp test using the same specimen. We subsequently compared the analysis success rates and detection rates between the two tests. Results: A total of 116 samples were identified. The success rates and detection rates of EGFR mutations in the total number of samples were 90% and 28%, respectively for the Oncomine Dx Target Test, and 100% and 35% for the PNA‐LNA PCR clamp test. The Oncomine Dx Target Test was unable to analyze three samples (2%) due to the samples not passing the nucleic acid concentration threshold, and nine (8%) samples had invalid results. The exon 19 deletion was not detected by the Oncomine Dx Target Test in four cases (4%). Conclusions: The analytical performance of the Oncomine Dx Target Test analysis for EGFR mutations may not be comparable with conventional single gene tests due to both invalid and false‐negative results. Key points: Significant findings of the study: The success rate of the Oncomine Dx Target Test was significantly lower than the PNA‐LNA PCR clamp test. Among the samples successfully analyzed, four exon 19 deletions were not detected by the Oncomine Dx Target Test. What this study adds: The analytical performance of the Oncomine Dx Target Test may not be comparable with conventional single gene tests. We should revise the sampling procedures, and review the sample quality assessment methods, to improve the analytical performance. Abstract : There have been few studies on the performance of the Oncomine Dx Target Test compared with a PNA‐LNA PCR clamp test. Here, we reviewed 116 samples and compared the success and detection rates of EGFR mutations. The rates of the Oncomine Dx Target Test were numerically lower than the PNA‐LNA PCR clamp test, and analytical performance between the two tests may therefore not be comparable.